(3OQQ GdaQGFO GdefXeI aj CNHGQ GdML hWQjb ecI GdecQeIs - (3YHO GdbGOQ Hf eMeO Hf YHO GdbGOQ Hf eMeO GdCfUGQj GdLRjQj,J (B977 (3g` s
(3ChdgG (B:s
(3Ef Chdi eG jJhL HPcQg QAhS GdcJH hGdOaGJQ s
(3BNQgG (B:s
(3hGddg GdeSFhd ai HdhZ GdeQGO hGdSDGd , hgh MSHi hfYe Gdhcjd s
(3VefgG CNHGQ GdMGL hEeQJg hGdefGRds
(3hcjajI GdQMhd hGdfRhd hGdefGgd hGdEbGeI hGdefGSc Ydi ePgH GdEeGe GHf MfHdhQJH GdMhGOK ajg Ydi GdSfjf GdgLQjIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B44 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B300s
Keywords: (3GdJGQjNs